2007
DOI: 10.1634/stemcells.2006-0532
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Reprogramming in Hybrids of Somatic Cells and Embryonic Stem Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 30 publications
(36 reference statements)
4
50
0
Order By: Relevance
“…the pluripotent phenotype becomes differentiated to a somatic-cell phenotype (Shimazaki et al, 1993) in a unidirectional process. Ambrosi et al showed that Journal of Cell Science 122 (22) the gene-expression profile of the fusion-hybrid cells is similar, but not identical, to that of the pluripotent cell partner (Ambrosi et al, 2007). Having assessed the transcriptional status of 36,601 transcripts encoded within the mouse genome, they categorized the genes in seven major clusters according to gene-expression patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the pluripotent phenotype becomes differentiated to a somatic-cell phenotype (Shimazaki et al, 1993) in a unidirectional process. Ambrosi et al showed that Journal of Cell Science 122 (22) the gene-expression profile of the fusion-hybrid cells is similar, but not identical, to that of the pluripotent cell partner (Ambrosi et al, 2007). Having assessed the transcriptional status of 36,601 transcripts encoded within the mouse genome, they categorized the genes in seven major clusters according to gene-expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…That is, pluripotent cells effectively reprogram somatic cells, abolishing the gene-expression patterns of the somatic cell and resetting the gene-expression profile to that of the pluripotent state. However, the gene-expression profile of the fusion-hybrid cells is similar, but not identical, to that of the pluripotent cell-fusion partner, indicating that fusion-induced reprogramming is a unidirectional process that occurs concomitantly with the incomplete reprogramming of certain genes (Ambrosi et al, 2007). Therefore, fusion-induced reprogramming does not necessarily result in the complete genetic reprogramming of somatic cells to a phenotype identical to that of the pluripotent cell-fusion partner.…”
Section: Introductionmentioning
confidence: 93%
“…Apart from oocytes, embryonic germ (EG) cells and embryonic stem cells (ESC) also contain factors that can reprogram somatic cell nuclei, as fusion of these cells with somatic cells creates tetraploid hybrids wherein silencing and activation of genes on somatic chromosomes occurs [5]. Although transcriptional differences exist between ESC and ESC/EG cell-somatic cell hybrids [6], the latter can generate embryoid bodies (EBs) and teratomas and contribute to chimeras when injected into the blastocyst [7,8]. The activation of the pluripotency-associated transcription factor (TF) Oct4 can also be achieved through the introduction of cellfree extracts from ESC and embryonic carcinoma (EC) cells, although full reprogramming to pluripotency has not been shown [9].…”
Section: Introductionmentioning
confidence: 99%
“…This provided a good indication that EC nuclear pluripotency is not abolished in the presence of a differentiated genome (Miller and Ruddle, 1976). Differentiation into derivatives of the ectoderm, mesoderm and endoderm was later confirmed when teratoma and embryoid bodies were derived from hybrid cells made from somatic and ESCs (Ambrosi et al, 2007;Cowan et al, 2005;Tada et al, 2003;Terada et al, 2002;Yu et al, 2006). When hybrid cells resulting from the fusion of thymocytes with either embryonic germ cells (EGCs) or ESCs were injected into mouse embryos they contributed to the three lineages of the resulting chimera at the embryonic stage (Tada et al, 1997;Tada et al, 2001).…”
Section: By Cell Fusionmentioning
confidence: 84%
“…Thus, sets of genes are expressed at similar levels in hybrid and somatic cells, but differently in ESCs, suggesting incomplete resetting of the somatic genome (Ambrosi et al, 2007;Cowan et al, 2005).…”
Section: Cell Fusionmentioning
confidence: 99%